Oral microbiota of Brazilian captive snakes - Fonseca, M. G.; Moreira, W. W. Q. [UNESP]; Cunha, K. C.; Ribeiro, A. C. M. G.; Almeida, M. T. G. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2009)
The present work aimed to determine the oral microbiotic composition of snakes from Sao Jose do Rio Preto city, São Paulo State, Brazil. Ten snake species, comprising the families Boidae, Colubridae, Elapidae and Viperidae, were submitted to microbiological examination of their oral cavity, which indicated positivity for all buccal samples. Gram-negative bacilli, gram-negative cocci bacilli, gram-positive bacilli and gram-positive cocci were isolated from the snakes. Among isolated bacterium species, the occurrence of coagulase-negative staphylococci in the buccal cavity of Crotalus durissus (Viperiade), Eunectes murinus (Boidae), Mastigodryas bifossatus (Colubridae) and Bacillus subtilis, common to oral cavity of Bothrops alternatus (Viperidae) and Phalotris mertensi (Colubridae), was detected. It was observed higher diversity of isolated bacteria from the oral cavity of Micrurus frontalis (Elapidae) and Philodryas nattereri (Colubridae), as well as the prevalence of gram-positive baccillus and gram-positive cocci. The composition of the oral microbiota of the studied snakes, with or without inoculating fangs, is diverse and also related to the formation of abscesses at the bite site in the victims of the ophidian accidents, and to pathogenic processes in the snakes that host these microorganisms.
Keywords: venomous snakes; non-venomous snakes; oral cavity; bacterial isolation; captive snakes